Nuclear-Order-Induced Quantum Criticality and Heavy-Fermion Superconductivity at Ultra-low Temperatures in YbRh2Si2 - Schuberth, Erwin; Wirth, Steffen; Steglich, Frank (Frontiers in Electronic Materials, 2022)
The tetragonal heavy-fermion metal YbRh2Si2 orders antiferromagnetically at TN = 70 mK and exhibits an unconventional quantum critical point (QCP) of Kondo-destroying type at BN = 60 mT, for the magnetic field applied within the basal (a, b) plane. Ultra-low-temperature magnetization and heat-capacity measurements at very low fields indicate that the 4f-electronic antiferromagnetic (AF) order is strongly suppressed by a nuclear-dominated hybrid order (“A-phase”) at TA ≤ 2.3 mK, such that quantum critical fluctuations develop at B ≈ 0 (Schuberth et al., Science, 2016, 351, 485–488). This enables the onset of heavy-fermion superconductivity (Tc = 2 mK) which appears to be suppressed by the primary antiferromagnetic order at elevated temperatures. Measurements of the Meissner effect reveal bulk superconductivity, with Tc decreasing under applied field to Tc < 1 mK at B > 20 mT. The observation of a weak but distinct superconducting shielding signal at a temperature as high as 10 mK suggests the formation of insulated random islands with emergent A-phase order and superconductivity. Upon cooling, the shielding signal increases almost linearly in temperature, indicating a growth of the islands which eventually percolate at T ≈ 6.5 mK. Recent electrical-resistivity results by Nguyen et al. (Nat. Commun., 2021, 12, 4341) confirm the existence of superconductivity in YbRh2Si2 at ultra-low temperatures. The combination of the results of Schuberth et al. (2016) and Nguyen et al. (2021) at ultra-low temperatures below BN, along with those previously established at higher temperatures in the paramagnetic state, provide compelling evidence that the Kondo-destruction quantum criticality robustly drives unconventional superconductivity.